Determinants of Goverment Financial Statement Quality Likelihood in Indonesian - N Nurcahyono; Luluk Muhimatul Ifada (Universitas Pendidikan Indonesia, 2024)
This research aims to analyze the factors determining the quality of local government financial report information during the pandemic, with its interaction with external pressure, environmental uncertainty, internal control and technology implementation on financial statement quality. The data was obtained within the Central Java Provincial Government from 20 October 2021 to 15 February 2022 using a survey method. The questionnaire responses were 257 from 35 Regional Government Organizations—data analysis technique using Structural Equation Modeling-Partial Least Square (SEM-PLS). The research results show that HR competency, compliance with accounting standards, information technology, internal pressure, environmental uncertainty and internal control directly affect the quality of financial report information during the pandemic. It was also found that external pressure and internal control were mediating variables that increased the relationship between variables. The greater the external pressure and the better the implementation of internal control, the better the quality of financial report information will be, as evidenced by an increase in R-square of 20 per cent. Theoretical implications confirm stewardship theory and can be used practically as material for government consideration to improve the quality of financial report information. The novelty of our research also lies in the use of environmental and economic uncertainty variables that occurred in Indonesia during the COVID-19 period. Hence, this research discusses the quality of financial reports comprehensively by combining various elements related to government regulations, company factors and psychological factors of accountants who are research respondents.